The Implementation of Broken Text Method to Improve Class X Arabic Learning Activity in MA al-Hikmah Kotamobagu - Ratni Bt. Hj. Bahri; Citra Asriyani Mokoagow; Zohra Yasin (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to determine student learning activity using the Broken Text method for class X MA Al-Hikmah Mogutat Kotamobagu, Academic Year 2021/2022. This method can be applied to train students in compiling a systematic script. This type of research uses classroom action research, which is carried out collaboratively. The research design used is the John Elliot model. This research was carried out in two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The research subjects were students of class X MIPA MA Al-Hikmah Kotamobagu, totaling 16 people and the object of this study was student learning activity. Data collection is done through observation and activity scale. The data analysis technique is descriptive qualitative and quantitative descriptive.The results showed that students' learning activity increased during the Arabic learning process using the Broken Text method. These results can be shown in the results of the pre-cycle research with a percentage of 49.13%, the first cycle action increased 62.81% and the second cycle action reached 75.13%. Thus, the use of the Broken Text method can increase student learning activities.